2014
DOI: 10.4028/www.scientific.net/amr.896.562
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Physico-Mechanical Properties of Eco-Friendly Composite Made from Bamboo

Abstract: This research focused on physical and mechanical properties of biocomposite made from bamboo and citric acid as natural binder. Bamboo particles was mixed with citric acid at 0 – 40 wt% resin content based on air-dried particles and each mixture was hot pressed at 180 °C for 10 min. The result showed that addition of citric acid could improve significantly the physical and mechanical properties of particleboard. The thickness swelling was 50 % for bamboo binderless particleboard (0 wt%), whereas it decreased t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 4 publications
1
10
0
6
Order By: Relevance
“…The intensity increased as the amount of citric acid and pressing temperature increased. A similar trend was found for bamboo particleboard bonded using citric acid at concentrations ranging from 10% to 40% (Widyorini et al 2014). The carbonyl group was present because of the reaction of the hydroxyl groups from the lignocellulosic materials and carboxyl groups from citric acid (Umemura et al 2011).…”
Section: Mechanical Propertiessupporting
confidence: 56%
“…The intensity increased as the amount of citric acid and pressing temperature increased. A similar trend was found for bamboo particleboard bonded using citric acid at concentrations ranging from 10% to 40% (Widyorini et al 2014). The carbonyl group was present because of the reaction of the hydroxyl groups from the lignocellulosic materials and carboxyl groups from citric acid (Umemura et al 2011).…”
Section: Mechanical Propertiessupporting
confidence: 56%
“…Recently, Umemura et al (2012) found that citric acid has good adhesivity for wood and elucidated the physical properties of particleboard bonded with citric acid (Umemura et al, 2013(Umemura et al, , 2014. Furthermore, particleboard produced using bamboo and citric acid was also evaluated and was found to have good physical properties (Widyorini et al, 2014). Citric acid (2-hydroxy-1,2,3-propanetricarboxylic acid) is an organic polycarboxylic acid containing three carboxyl groups.…”
mentioning
confidence: 99%
“…Hal ini diduga karena penambahan asam sitrat dan asap cair sebagai pelarut pada partikel kulit kacang tanah dapat merubah warna dari papan partikel yang dihasilkan. Hal yang sama juga ditemukan oleh Widyorini et al (2014) yang meneliti papan partikel dari bambu dengan penambahan asam sitrat dan Umemura et al (2011) yang meneliti produk cetakan kayu akasia dengan penambahan asam sitrat.…”
Section: Hasil Dan Pembahasan Sifat Fisika Dan Mekanika Papan Partikelunclassified